Shaping comparative advantage: the evolution of trade and industry policy in Australia - Fenna, Alan (Taylor and Francis, 2016)
© 2016 Australian Political Studies Association. This paper provides an overview of Australia’s experience with trade and industry policy since Federation in light of the dilemmas facing a small, rich, remote, resource-based economy. It focuses on the attempt to diversify away from a dependence on the export of primary products and to move beyond – while still also continuing to exploit – the country’s natural comparative advantage. It examines the rise and decline, purpose and effects, of protectionism; moments of experimentation with interventionist industry policy; and effects of the mining boom. In doing so, it considers Australia’s particular economic circumstances and factor endowments in light of competing notions of comparative advantage and the appropriate role of government in promoting economic development and competitiveness.